COMMUNICATION, WORK DISCIPLINE AND COMPETENCE ON INCREASING VALUE OF EVALUATION RESULTS ON PERFORMANCE REPORT OF GOVERNMENT INSTITUTIONS (LAKIP) KABUPATEN KERINCI GOVERNMENT - Juita, Yusmala (Archives of Business Research, 2019)
This study aimed to determine and analyze the partial and simultaneous effect of Communication, Work Discipline and Competence on increasing value of evaluation results in Accountability and Performance Report of Government Institution (LAKIP) Kabupaten Kerinci Government. This research was carried out in the Regional Government of Kabupaten Kerinci, with 96 respondents which consisted of the Head of the OPD, the Sub-division Head of the OPD Program and the facilitation preparing team of performance report in the Kabupaten Kerinci Government. To collect the data, this study used observations, questionnaires and interviews. The analysis technique used in this study was multiple linear regressions to test the correlation between variables, between dependent and independent variables. The results of the study shown that partially and simultaneously, communication, work discipline and competence have a significant effect on the increasing value of the evaluation results in Accountability and Performance Report of Government Institutions (LAKIP) the Kabupaten Kerinci Government.